Cenozoic tectono-geomorphological growth of the SW Chinese Tian Shan: Insight from AFT and detrital zircon U–Pb data. (1st November 2015) - Jia, Yingying; Fu, Bihong; Jolivet, Marc; Zheng, Shuo
Highlights: The deformation of the SW Chinese Tian Shan initiated at 35–25 Ma, and migrated southward at ∼15 Ma. The Atushi and Aksai Basin were separated into two independent basins since the mid-Miocene. The thrust system in the study area was likely transferred from the Talas-Fergana fault since middle Miocene. Abstract: As a unique example of the intracontinental mountain building, the Cenozoic deformation of the Tian Shan has been widely studied. The onset of Cenozoic exhumation of the SW Chinese Tian Shan was constrained at the Oligocene–Miocene boundary. However, the Cenozoic tectono-geomorphological growth process of the SW Chinese Tian Shan and adjacent piedmont basins remains a challenge. In this study, we carried out the geological mapping of satellite images and field investigations together with the apatite fission track (AFT) and detrital zircon U–Pb analyses to get further understanding of the Cenozoic tectonic deformation and geomorphological growth of the SW Chinese Tian Shan. Our results indicate that the exhumation of the hanging wall of Maidan fault or topography growth of the Kokshaal Range commenced in the late Eocene–Oligocene (35–25 Ma). Then, the structural deformation migrated southward to the Muziduke fault and the Atushi Basin Thrust (ABT) at ∼15 Ma. The growth strata of 6–3 Ma on the south flank of Keketamu Anticline imply that tectonic deformation propagates further basinward. Furthermore, the uplift of the Kokshaal Range also strongly affected the evolution of piedmont basins. The results suggest that the Atushi Basin was still likely linked to the Aksai Basin during the early Miocene. They were separated into two independent basins since ca. 13.7–10.5 Ma, as a response to the rapid uplift of the Kokshaal Range. Finally, we infer that the southeastern part of dextral Talas-Fergana fault (TFF) is likely transferred to the NEE-trending thrust faults of the SW Chinese Tian Shan since ∼15 Ma.